Sylvia Plath : comprehensive research and study guide - Bloom, Harold (Broomall, PA : Chelsea House Publishers, 2001)
Presents biographical information on twentieth-century American poet Sylvia Plath and profiles five of her works, providing thematic analysis and excerpts of criticism; also includes primary and secondary bibliographies.
Includes bibliographical references (p. 91-93) and index.
School Library Journal.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Plath, Sylvia -- Criticism and interpretation -- Handbooks, manuals, etc; Plath, Sylvia -- Examinations -- Study guides; Plath, Sylvia -- Criticism -- Handbooks, manuals, etc; Plath, Sylvia -- Examinations -- Study guides